Kentucky Folk Architecture. - Montell, William Lynwood, 1931- (The Kentucky bicentennial bookshelf Kentucky folk architecture, 1995)
A concise and amply illustrated introduction to Kentucky folk structures--log cabins, houses, cribs, and barns--that should be treasured as irreplaceable expressions of the cultural values of the Commonwealth's past.